Reformulasi Pengaturan Penyelenggaraan Tabungan Perumahan Rakyat Dalam Pemotongan Upah Pekerja (RechtJiva, 2025)
The Indonesian government issued Law No. 4 of 2016 on Public Housing Savings to address the limitations of the housing finance system. Unfortunately, this regulation has caused controversy because the provision requires wage deductions for all workers earning above the minimum wage, including those who already own a house. This creates injustice and conflicts with other regulations. Based on these problems, this research raises the issue of (1) Why is there a conflict in Law Number 4 of 2016 concerning Public Housing Savings and Regulations with higher laws and regulations related to the imposition of wage deductions? (2) How to reformulate the regulation on the implementation of Public Housing Savings in cutting workers' wages in the future that is not detrimental to laborers. This research uses a normative juridical method by utilizing three types of approaches, namely the statutory approach, conceptual approach, and comparative approach. The result of this research is that there is a legal conflict between the Public Housing Savings policy and other regulations due to conflict and incompatibility. The policy formulation can be done by removing the regulation of Public Housing Savings and replacing it with MLT BPJS Ketenagakerjaan, or at least revised to make it compatible by including workers in its formulation so that it is more in line with the needs of workers.